On the Importance of Default Breach Remedies - Randolph Sloof; Hessel Oosterbeek; Joep Sonnemans (Tinbergen Institute, 2006)
Theory predicts that default breach remedies are immaterial whenever contracting costs are negligible. Some experimental studies, however, suggest that in practice default rules do matter, as they may affect parties' preferences over contract terms. This paper presents results from an experiment designed to address the importance of default breach remedies for actual contract outcomes. We find that default rules do have an influence. The reason for this is not that contract proposals and/or responses are biased towards the default, but rather that parties often disagree over what the best contract is and therefore end up with the default.
Keywords: K12; C91; 330; breach remedies; default remedies; experiments